2021
DOI: 10.1021/acs.nanolett.1c03493
|View full text |Cite
|
Sign up to set email alerts
|

Gate-Controlled Supercurrent in Epitaxial Al/InAs Nanowires

Abstract: Gate-controlled supercurrent (GCS) in superconducting nanobridges has recently attracted attention as a means to create superconducting switches. Despite the clear advantages for applications, the microscopic mechanism of this effect is still under debate. In this work, we realize GCS for the first time in a highly crystalline superconductor epitaxially grown on an InAs nanowire. We show that the supercurrent in the epitaxial Al layer can be switched to the normal state by applying ≃±23 V on a bottom gate insu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
28
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 78 publications
9
28
2
Order By: Relevance
“…Recently, gate voltage (V g ) induced bipolar full supercurrent suppression was demonstrated via conventional solid gating in several metallic superconducting nanostructures, such as wires, 3,4 constriction Josephson junctions, 5 and proximitized normal metals. 6 Similar results were also obtained on suspended 7 and epitaxial 8 superconducting metal layers grown on semiconductor nanowires. Differently from charge accumulation/depletion, this gating effect also seems to influence the phase of the Cooper pair condensate 9−11 without apparent impact on T C and R N , 12 thereby suggesting a nontrivial interaction between electrostatic fields and superconductivity.…”
supporting
confidence: 78%
“…Recently, gate voltage (V g ) induced bipolar full supercurrent suppression was demonstrated via conventional solid gating in several metallic superconducting nanostructures, such as wires, 3,4 constriction Josephson junctions, 5 and proximitized normal metals. 6 Similar results were also obtained on suspended 7 and epitaxial 8 superconducting metal layers grown on semiconductor nanowires. Differently from charge accumulation/depletion, this gating effect also seems to influence the phase of the Cooper pair condensate 9−11 without apparent impact on T C and R N , 12 thereby suggesting a nontrivial interaction between electrostatic fields and superconductivity.…”
supporting
confidence: 78%
“…For strong enough electric fields normal metal behaviour was observed. This phenomenon is known as the Superconductive Field Effect (SFE) and the results have been recently confirmed by other experimental groups [5][6][7][8][9][10][11].…”
mentioning
confidence: 54%
“…The microscopic origin of this phenomenon is unclear. All the materials [2,[5][6][7][8][9][10][11] analyzed are well described by the conventional BCS theory and metallic in the normal phase (hence it is surprising that the electrostatic field could play any role). It has been suggested that energetic quasi-particle injection from the gate control [6,7] or energy or phase fluctuations [9] could be responsible for the observations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, gate voltage (V g ) induced bipolar full supercurrent suppression was demonstrated via conventional solid gating in several metallic superconducting nanostructures, such as wires [3], constriction Josephson junctions [4], and proximitized normal metals [5]. Similar results were obtained also on suspended [6] and epitaxial [7] superconducting metal layers grown on semiconductor nanowires. Differently from charge accumulation/depletion, this gating effect seems to influence as well the phase of the Cooper pairs condensate [8][9][10] without apparent impact on T C and R N [11], thereby suggesting a non-trivial interaction between electrostatic fields and superconductivity.…”
mentioning
confidence: 63%